Možnosti financování inovací v malých a středních podnicích - Vavrys, Ondřej (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Předmětem bakalářské práce „Možnosti financování inovací v malých a středních podnicích“ je popis zamýšlené produktové inovace ve společnosti a návrh možného financování. V teoretické části práce jsou vysvětleny pojmy související s inovacemi a možnosti financování podnikových aktivit. Praktická část je zaměřena na charakteristiku vybrané společnosti a možné varianty financování zamýšlené inovace. Závěr práce obsahuje hodnocení a návrh řešení daného problému.

The subject of bachelor thesis „Possibilities of financing innovations in Small and Medium Enterprises“ is a description of thoughtful product innovation and suggestions of possible ways of financing it. In the theoretical part of the thesis terms related to innovation and possibilities of financing business activities are explained. The practical part is focused on the characteristics of the selected company and the proposal of financing the intended Innovation. The conclusion contains an evaluation and a proposal for solving the problem.
Possibilities of financing innovations in Small and Medium Enterprises
Keywords: Podnik; inovace; inovační proces; financování; náklady; zdroje; Company; innovation; innovation proces; financing; costs; sources